2018
DOI: 10.4236/ampc.2018.89023
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Thermal, Rheological, Morphological and Mechanical Properties of Biocomposites Based on Rod-Of Typha/HDPE Made up of Typha Stem and HDPE

Abstract: The thermal, rheological and morphological properties of composite biomaterials made with mixture of high density polyethylene and typha rod powder (RD) were evaluated. The dynamic mechanical behavior of the samples was studied with 25%, 35% and 45% typha stem powder concentrations. The viscoelastic properties are mainly related to the nature of the polymer and the typha stem powder. Storage (G') and loss (G") moduli increased significantly, depending on the amount of powder in the molten mixture. After a visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Additionally, solid carbon residue is not formed despite an inert atmosphere, which is a common behavior of Pes, as reported in the literature [ 110 ]. The behavior of HDPE at 250–300 °C, at the beginning of HDPE degradation, is a common behavior of HDPE in TGA measurements, as presented in the literature [ 111 , 112 ]. In the nanocomposites, this behavior disappeared in the presence of TiN particles.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, solid carbon residue is not formed despite an inert atmosphere, which is a common behavior of Pes, as reported in the literature [ 110 ]. The behavior of HDPE at 250–300 °C, at the beginning of HDPE degradation, is a common behavior of HDPE in TGA measurements, as presented in the literature [ 111 , 112 ]. In the nanocomposites, this behavior disappeared in the presence of TiN particles.…”
Section: Resultsmentioning
confidence: 99%
“…The behavior of the biofiller networks, at higher filler loading, at low and high frequencies is shown in Figure 13. Several authors have reported on the rheological percolation 52,53 …”
Section: Resultsmentioning
confidence: 99%